Pengaruh Korupsi dan Pendapatan Nasional terhadap Pembangunan Ekonomi di Negara-negara Islam - Andri Martiana (Islamic Economics Journal, 2016)
Economic development was an attempt by the state to improve the welfare of people in the entire region. Some effort of this development are the expansion of the economic base with diversification of agriculture, the development of production of extractive (mining, forestry) development of secondary industry (manufacturing and construction) and the activities of the tertiary sector (services) as well as the creation of productive employment in the fields of widespread activity.There are some fundamental issues in economic development, some of which are problems of corruption and economic growth as an increased ability to produce goods and services in various fields. This study aimed to analyze the effects of corruption and the national income to economic development in the Islamic countries. The study was conducted in Islamic countries who are members of the Organization of Islamic Conference (OIC) to take a sample of 52 countries members of the Organization of Islamic Conference (OIC) which was analyzed by quantitative approach using a multiple linear regression analysis. From the analysis, discussion and hypothesis testing using corruption and national income variables as independent variables, and economic development as the dependent variable, the results of studies showed that the corruption variables have positive and significant influence amounted to 42.1% of the economic development. National income variable has a positive and significant effect of 0.5% on economic development. Variable corruption and national income together (simultaneously) has a positive and significant influence amounted to 33.0% of the variable economic development.